A novel water-soluble sulfonated porphyrin fluorescence sensor for sensitive assays of H2O2 and glucose1. Issue 5 (7th March 2015) - Huan, Y. F.; Fei, Q.; Shan, H. Y.; Wang, B. J.; Xu, H.; Feng, G. D.
<x xml:space="preserve">Abstract</x> A water-soluble sulfonated porphyrin (H2TEHPPS) was used to build a novel platform for sensitive assays of H2O2 and glucose.